Layered double hydroxide-seaweed composites promote seed germination and seedling growth: a new generation of biostimulants - Espinosa-Antón, Adrian Alejandro; Hernández-Herrera, Rosalba Mireya; Sánchez-Hernández, Carla Vanessa; Carbajal-Arízaga, Gregorio Guadalupe; Rodríguez-Zaragoza, Fabián Alejandro (Frontiers in Plant Science, 2025)
IntroductionAgricultural producers worldwide face increasing pressure to ensure food security while contending with the adverse effects of climate change and unsustainable farming practices. Layered double hydroxides (LDHs) have been applied in agriculture due to their versatile properties as slow-release and efficient carriers, while seaweed extracts are widely used as plant biostimulants. However, their integrated use as nanostructured composites for enhancing seed germination and seedling growth remains largely unexplored.MethodsIn this study, we addressed this gap by synthesizing composites that combine cationic LDH nanosheets with anionic compounds present in alkaline extracts of the brown seaweed Sargassum liebmannii (LDH-Sargassum) and the green seaweed Ulva ohnoi (LDH-Ulva). The physicochemical properties of the LDH-seaweed composites were characterized using X-ray diffraction (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), Fourier-transform infrared spectroscopy (FT-IR), dynamic light scattering (DLS), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS). The biological efficacy of the composites was evaluated through seed germination and early seedling development assays in tomato (Solanum lycopersicum L. cv. Rio Grande) and root induction assays in mung bean (Vigna radiata L.) cuttings.ResultsPhysicochemical analyses confirmed that approximately 12% of the composite mass corresponded to seaweed-derived molecules adsorbed onto the LDH surface. Both LDH-Sargassum and LDH-Ulva significantly improved germination and seedling growth at lower concentrations (1.57, 3.14, and 6.28 mg·mL⁻¹), while higher doses (12.56–50.25 mg·mL⁻¹) produced effects that were either comparable to those of the control or slightly better. Notably, both composites enhanced root architecture in mung bean cuttings by increasing root number, length, and dry weight. These results highlight the potential of LDH-seaweed composites as effective biostimulants, particularly in promoting early-stage root development by improving root branching, size, and biomass. Importantly, LDH-Sargassum at 6.28 mg·mL⁻¹ emerged as a promising natural alternative to synthetic root-promoting agents.DiscussionThis study demonstrates, for the first time, the feasibility of LDH-seaweed composites as next-generation nanostructured phycobiostimulants, providing insights into their plant interactions and identifying optimal application dosages. Overall, these findings provide a foundation for implementing LDH-seaweed composites as a sustainable strategy to reduce agrochemical inputs and advance towards food security through bio-based nanotechnologies.